ANALISIS SEMIOTIKA CHARLES SANDERS PIERCE DALAM NOVEL ZIARAH KARYA IWAN SIMATUPANG - Tika Sari; Liza Septa Wilyanti (Universitas Batanghari, 2022)
This study aims to explain the meaning in the novel Ziarah by Iwan Simatupang by looking at the signs in the novel. The method used in this research is a qualitative method. The source of this research is the novel Ziarah by Iwan Simatupang. The data in this study are in the form of words in the novel Ziarah by Iwan Simatupang about the signs in the novel. The theory used in this study is the semiotic concept of Charles Sanders Pierce. According to Charles Sanders Pierce in the process of meaning there are three stages, namely representament, object, and interpretant. Based on the signs that have been found, the novel Ziarah by Iwan Simatupang has a meaning, namely death. From the meaning of this novel, it wants to describe social criticism. Where in this life we will face something that is certain, namely death. Everyone will experience it like it or not, and like it or not. Human awareness about death is still in the form of fear and anxiety. Suggestions for this research are that it is necessary to study more deeply and add data to strengthen the analysis. The researcher gives suggestions for further researchers who want to analyze using the object of the novel Ziarah by Iwan Simatupang to use a different approach to add broader knowledge.